Trigonometric identities via combinatorics - Bényi, Beáta (Teaching Mathematics and Computer Science, 2019)
In this paper we consider the combinatorial approach of the multi-angle formulas sin nΘ and cos nΘ. We describe a simple "drawing rule" for deriving the formulas immediately. We recall some theoretical background, historical remarks, and show some topics that is connected to this problem, as Chebyshev polynomials, matching polynomials, Lucas polynomial sequences. Subject Classification: 05A19